2005
DOI: 10.1111/j.1755-0238.2005.tb00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a simple indicator of water stress in grapevine (Vitis vinifera L.) based on the differential sensitivities of vegetative growth components

Abstract: Responses of grapevine vegetative growth components to mild, medium and severe soil water deficits were used to identify simple and sensitive indicators for early diagnosis of water stress. Soil water deficit was characterised as the fraction of transpirable soil water (FTSW) remaining in a water‐depleted rootzone. Growth components included the number of emerged leaves on first (Ist) and second (IInd) order lateral branches, the leaf area and internode length of each phytomer of Ist order lateral branches, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(79 citation statements)
references
References 28 publications
7
68
2
2
Order By: Relevance
“…The phenological changes in the sink-source relations are then a particularly important factor to consider when attempting to use TGR as a water stress indicator. Recently, some reports (Hardie and Martin 2000;Pellegrino et al 2005) have suggested monitoring shoot growth of defruited vines for irrigation scheduling, mainly to avoid the interaction between fruit and vegetative growth. In this sense TGR might behave similarly as shoot growth of a de-fruited vine.…”
Section: Discussionmentioning
confidence: 99%
“…The phenological changes in the sink-source relations are then a particularly important factor to consider when attempting to use TGR as a water stress indicator. Recently, some reports (Hardie and Martin 2000;Pellegrino et al 2005) have suggested monitoring shoot growth of defruited vines for irrigation scheduling, mainly to avoid the interaction between fruit and vegetative growth. In this sense TGR might behave similarly as shoot growth of a de-fruited vine.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, drought was applied by withholding water when the first pod appeared at the beginning of pod filling and seed-filling. Also in these stages total leaf water potential was used as the index of soil water status according to Williams and Araujo (2002) and Pellegrino et al (2005). Total leaf water potential was measured using a pressure chamber (PMS, Instrument Company, Corvallis, Oregon).…”
Section: Methodsmentioning
confidence: 99%
“…Leaf number is an easily measured and non-destructive external index that enables comparison among plants grown in different environments (Zalesny et al 2007). Earlier studies have explored the relationship between leaf number, plant growth and stress tolerance (e.g., Kodani 1999, Pellegrino et al 2005), but our study is among the first to find a clear correlation among these factors. More studies are needed but the basis for salt tolerant selections could come initially from leaf counts.…”
Section: Discussionmentioning
confidence: 46%